Clinical Characteristics, Diagnostic Evaluation, and Antibiotic Prescribing Patterns for Skin Infections in Nursing Homes - Yogo, Norihiro; Gahm, Gregory; Knepper, Bryan C.; Burman, William J.; Mehler, Philip S.; Jenkins, Timothy C. (Frontiers in Medicine, 2016)
Background The epidemiology and management of skin infections in nursing homes has not been adequately described. We reviewed the characteristics, diagnosis, and treatment of skin infections among residents of nursing homes to identify opportunities to improve antibiotic use. Methods This was a retrospective study involving 12 nursing homes in the Denver metropolitan area. For residents at participating nursing homes diagnosed with a skin infection between July 1, 2013 and June 30, 2014, clinical and demographic information was collected through manual chart review. Results Of 100 cases included in the study, the most common infections were non-purulent cellulitis (n = 55), wound infection (n = 27), infected ulcer (n = 8), and cutaneous abscess (n = 7). In 26 cases, previously published minimum clinical criteria for initiating antibiotics (Loeb criteria) were not met. Most antibiotics (n = 52) were initiated as a telephone order following a call from a nurse, and 41 patients were not evaluated by a provider within 48 h after initiation of antibiotics. Nearly all patients (n = 95) were treated with oral antibiotics alone. The median treatment duration was 7 days (interquartile range 7–10); 43 patients received treatment courses of ≥10 days. Conclusion Most newly diagnosed skin infections in nursing homes were non-purulent infections treated with oral antibiotics. Antibiotics were initiated by telephone in over half of cases, and lack of a clinical evaluation within 48 h after starting antibiotics was common. Improved diagnosis through more timely clinical evaluations and decreasing length of therapy are important opportunities for antibiotic stewardship in nursing homes.